Legalism : property and ownership - Kantor, Georgy, 1980-; Lambert, T. B. (Thomas Benedict), 1981-; Skoda, Hannah, 1981- (Oxford : Oxford University Press, 2018)
In this volume, ownership is defined as the simple fact of being able to describe something as 'mine' or 'yours', and property is distinguished as the discursive field which allows the articulation of attendant rights, relationships, and obligations. Property is often articulated through legalism as a way of thinking that appeals to rules and to generalizing concepts as a way of understanding, responding to, and managing the world around one. An Aristotelian perspective suggests that ownership is the natural state of things and a prerequisite of a true sense of self. An alternative perspective from legal theory puts law at the heart of the origins of property. However, both these points of view are problematic in a wider context, the latter because it rests heavily on Roman law.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 14, 2017).
Keywords: Right of property -- History; Property (Roman law); Economics; Economics